Mussoorie and its Plants: a Preliminary Survey - Raizada, M. B. (Indian Forester, 1959)
Mussoorie has a very rich and varied flora. Nearly 1200 species of Phanerogams and 136 ferns have been reported from an area of about 120 sq. miles and between 3000-7,500 ft. Collett reports 1,326 species of flowering plants and 124 ferns frotn Simla but he takes into consideration an area of about 500 sq. miles with a range of altitude from 2-10,000 ft. On the whole the trees and shrubs of the two regions are the same but Mussoorie has about 20 inches more rain during the monsoon which makes possible a varied epiphytic flora of lichens, liverworts, mosses, ferns and higher plants. In addition Mussoorie is much richer in orchids, aroids, and Gesneraceae. Conifers are much less numerous and important about Mussoorie than they are in the Simla region. Only Pinus roxburghii (Pinus longifolia) is abundant. Quercus incana is the chief tree from 5,000 ft. to the top of the ridges. Most of the trees above 5,000 ft. are broad leaved sclerophylls as eight months of the year are comparatively dry. There is a great variety of trees and shrubs in the Sub-Himalayan tract from 3,000 ft. to the zone of the oaks but none are very large. Only Pinus raxburghii is common in pure stands. Although the collector is not likely to find new species of higher plants about Mussoorie there probably still remain a number of species to be found in the lower valleys which have not yet been listed as occurring in the area.